The β2-adrenergic receptor in the apical membrane of intestinal enterocytes senses sugars to stimulate glucose uptake from the gut - Paulussen, Frederik; Kulkarni, Chetan P.; Stolz, Frank; Lescrinier, Eveline; De Graeve, Stijn; Lambin, Suzan; Marchand, Arnaud; Chaltin, Patrick; In't Veld, Peter; Mebis, Joseph; Tavernier, Jan; Van Dijck, Patrick; et al. (Frontiers in Cell and Developmental Biology, 2023)
The presence of sugar in the gut causes induction of SGLT1, the sodium/glucose cotransporter in intestinal epithelial cells (enterocytes), and this is accompanied by stimulation of sugar absorption. Sugar sensing was suggested to involve a G-protein coupled receptor and cAMP - protein kinase A signalling, but the sugar receptor has remained unknown. We show strong expression and co-localization with SGLT1 of the beta2-adrenergic receptor (beta2-AR) at the enterocyte apical membrane and reveal its role in stimulating glucose uptake from the gut by the sodium/glucose-linked transporter, SGLT1. Upon heterologous expression in different reporter systems, the beta2-AR responds to multiple sugars in the mM range, consistent with estimated gut sugar levels after a meal. Most adrenergic receptor antagonists inhibit sugar signaling, while some differentially inhibit epinephrine and sugar responses. However, sugars did not inhibit binding of I125-cyanopindolol, a beta2-AR antagonist, to the ligand-binding site in cell-free membrane preparations. This suggests different but interdependent binding sites. Glucose uptake into everted sacs from rat intestine was stimulated by epinephrine and sugars in a beta2-AR-dependent manner. STD-NMR confirmed direct physical binding of glucose to the beta2-AR. Oral administration of glucose with a non-bioavailable beta2-AR antagonist lowered the subsequent increase in blood glucose levels, confirming a role for enterocyte apical beta2-ARs in stimulating gut glucose uptake, and suggesting enterocyte beta2-AR as novel drug target in diabetic and obese patients. Future work will have to reveal how glucose sensing by enterocytes and neuroendocrine cells is connected, and whether beta2-ARs mediate glucose sensing also in other tissues.